The use of rosuvastatin and alpha lipoic acid in patients with unstable angina - E.H. Zaremba (Danylo Halytsky Lviv National Medical University, 2017)
Aim. To investigate the blood lipid profile, indices of functional condition of the liver in patients with unstable angina in the treatment of statins in combination with alpha lipoic acid.